Prevalence of nosocomial infections in Lordegan Shohada hospital from 2017 to 2022 - Sadeq Hosseinpour; Mohammad Moein Derakhshan Barjoei; Reyhane Izadi; Hossein Mahmudi; Toran Shahani; Masoumeh Sadat Mousavi (Journal of Preventive Epidemiology)
Introduction: Healthcare-acquired infections or nosocomial infections are a common problem in all countries. Objectives: The aim of this study was to conduct an epidemiological evaluation of nosocomial infections in Lordegan Shohada hospital from 2017 to 2022. Methods: This study was descriptive-analytical cross-sectional. The case finding was based on Centers for Disease Control (CDC) definitions for nosocomial infection and the nosocomial infection questionnaire of the Ministry of Health and medical treatment of Iran. Cases of nosocomial infection were confirmed based on clinical findings and tests then registered in the Iranian nosocomial infection surveillance system. Results: Overall, 48343 patients were at risk for nosocomial infections during the study period; of these, 274 (0.6%) cases of nosocomial infections were detected, of which 132 were men (48%), and 142(52%) were women. The most common type of nosocomial infection in this study was surgical site infections (0.33%), pneumonia (0.27%), and ventilator-associated events (0.10). The highest rate of nosocomial infection was reported from intensive care units (0.2). Conclusion: The prevalence of nosocomial infections in this center has been low compared to the global norm. This is not the reason that the majority of nosocomial infections are low. The most important reason was the irrational use of antibiotics and, therefore, the hiding of infection cases. The prevalence of microbial resistance is increasing since this issue is worrying in nosocomial infection control.